THE INFLUENCE OF GOITROGENS AND ENVIRONMENTAL FACTORS ON THE REPRODUCTIVE SYSTEM OF WOMEN WITH ENDEMIC THYROID DISEASES - Payenok, O.S.; Payenok, A.V.; Zadorozhnyj, A.M. (World of Medicine and Biology, 2017)
To study the dynamics of growth and prevalence of thyroid diseases during pregnancy, childbirth and the postpartum period in women under the influence of endemic iodine deficiency and anthropogenic factors. The analysis of morbidity among pregnant women, complications in childbirth in women of Western Ukraine. The study indicates that the prevalence of endemic goiter in seven regions of Western Ukraine during the gestation period is in direct proportional connection not only with natural iodine deficiency. Special attention is paid to the impact of technogenic pollution, additional goitrogens, iodine radioactive isotopes on thyroid gland morbidity. These findings suggest the need for an integrated approach to the wide prevention of thyroid gland pathology and the systematic monitoring of its effectiveness for improving the reproductive health and reducing perinatal complications.